Politicizing the Internet: getting women on-line. - Crow, Barbara (WE International)
The writer describes an approach that could supply the conditions and opportunities to convince women to use the Internet. She translates feminist investigations of gender and technology to the feminist practice of getting women on-line. In addition, she describes a number of workshops concerning the Internet that she offers on university campuses in the U.S. and Canada. She concludes that the problem is how to influence women who do not partake in workshops and who continue to have an ambivalent relationship to computers.